(untitled) (Comprehensive Journal of Science, 2026)
Background: Fluoride is a naturally occurring element in drinking water that has both beneficial and adverse effects on human health. While optimal levels prevent dental caries, excessive fluoride intake can lead to dental and skeletal fluorosis. In western Libya, few studies have evaluated fluoride concentrations and their associated health outcomes. Objectives: This study aims to assess the levels of fluoride in drinking water across three locations—Al-Jmail, Raqdalin, and Zuwara—in the western region of Libya. Additionally, it examines the prevalence of health effects associated with fluoride exposure among local residents through a structured community survey. Methods: A total of 200 water samples were collected from municipal networks, bore wells, and household wells. Fluoride concentrations were determined using an ion-selective electrode method, calibrated with standard solutions. A community survey was conducted with 300 participants to gather data on water consumption, source usage, and health outcomes such as dental staining and joint complaints. Statistical analysis included descriptive statistics, correlation analysis, and risk assessment using the Hazard Quotient (HQ) for different age groups. Results: Fluoride concentrations varied significantly across the three locations, with Al-Jmail recording the highest mean level (1.82 mg/L), followed by Raqdalin (1.42 mg/L) and Zuwara (0.91 mg/L). Approximately 42% of samples from Al-Jmail exceeded WHO recommended limits. Survey findings indicated a higher prevalence of dental fluorosis among children (38%) and skeletal complaints among adults (12%). A positive correlation was observed between higher fluoride concentrations and health outcomes, particularly in Al-Jmail. Conclusions: The study highlights significant variability in fluoride concentrations in western Libya, with potential health risks in areas exceeding safe levels. Integrating water analysis with community surveys provides a comprehensive assessment of exposure and health impact, emphasizing the need for preventive measures, including water treatment and public health education.